2007
DOI: 10.1089/ham.2007.1030
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Supply and Fiber Morphometry in Rat Myocardium after Intermittent Exposure to Hypobaric Hypoxia

Abstract: Panisello, Pere, Joan Ramon Torrella, Teresa Pagés, and Ginés Viscor. Capillary supply and fiber morphometry in rat myocardium after intermittent exposure to hypobaric hypoxia. High Alt. Med. Biol. 8:322-330, 2007.-Three groups of male rats were submitted to an intermittent hypobaric hypoxia (IHH) program for 22 days (4 h/day, 5 days/week) in a hypobaric chamber at a simulated altitude of 5000 m. Hearts were removed at the end of the program (H group) and 20 and 40 days later (P20 and P40 groups). A control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
6
11
3
Order By: Relevance
“…Previous work on myocardium muscle showed a progressive increase from C to H to P20 in capillary and Wbre densities associated with signiWcant reductions in Wbre area, perimeter and diVusion distances (Panisello et al 2007). Those results contrast with the results obtained in the present study due to the diVerent oxidative demands of the three muscles (myocardium, TA and DG) considered.…”
Section: Hypoxia and Muscle Workloadcontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous work on myocardium muscle showed a progressive increase from C to H to P20 in capillary and Wbre densities associated with signiWcant reductions in Wbre area, perimeter and diVusion distances (Panisello et al 2007). Those results contrast with the results obtained in the present study due to the diVerent oxidative demands of the three muscles (myocardium, TA and DG) considered.…”
Section: Hypoxia and Muscle Workloadcontrasting
confidence: 99%
“…With this approach in mind, we developed animal experiments using techniques and methods that cannot be used on humans for ethical or technical reasons. In a recent work we applied an IHHE protocol to laboratory rats in order to study myocardial morphofunctional parameters (Panisello et al 2007). Our Wndings indicate that the programme induces an adaptive response in rat myocardium for more eYcient O 2 delivery to the mitochondria of cardiac muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…A clear diminution of soleus muscle capillarization was observed, accompanied by a similar, but less marked, trend in extensor digitorum longus muscle. This decrease in the number of capillaries per mm 2 in both muscles does not agree with the findings of most studies on hypoxia effects (Valdivia, 1958;Banchero, 1975;Banchero et al 1976), including studies previously undertaken in our laboratory (Panisello et al 2007). However, the present results are in partial agreement with the few studies on anaemia and capillary density (Celsing et al 1988).…”
Section: Discussioncontrasting
confidence: 85%
“…Michel et al [26] reported a relationship of 1 capillary to 4 cardiomyocytes in domestic chickens, 1:6 in domestic ducks and 1:9 in pheasants. In the mammalian heart the number of capillaries per mm 2 was reported as about 2000–4000 in the human [27, 28] and rat [29, 30], 5000 capillaries in sheep [31] and 2500 in the Yak [32]. These results indicate the large range of these allied parameters among different species.…”
Section: Discussionmentioning
confidence: 99%